Understanding limb necrotizing infections: A comprehensive approach - A. Garrido-Hidalgo; J. García-Coiradas; M. Echevarría-Marín; S. Llanos; J.A. Valle-Cruz; F. Marco (Revista Española de Cirugía Ortopédica y Traumatología)
Introduction: Necrotizing soft tissue infections (NSTI) are increasing, posing a significant risk of morbidity and mortality. Due to nonspecific symptoms, a high index of suspicion is crucial. Treatment involves a multidisciplinary approach, with broad-spectrum antibiotics, early surgical debridement, and life support. This study analyzes the characteristics, demographics, complications, and treatment of NSTI in a hospital in Madrid, Spain. Methods: A retrospective observational study was conducted, including all surgically treated NSTI patients at our center from January 2016 to December 2022, examining epidemiological and clinical data. The Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) was prospectively calculated for all patients. Results: Twenty-two patients (16 men, 6 women, mean age 54.8) were included. Median time from symptom onset to emergency room visit was 3.5 days. All reported severe treatment-resistant pain; sixteen had fever exceeding 37.8 °C (72.7%). Skin lesions occurred in twelve (54.5%), and thirteen had hypotension and tachycardia (59.1%).Treatment involved resuscitative support, antibiotherapy, and radical debridement. Median time to surgery was 8.25 h. Intraoperative cultures were positive in twenty patients: twelve Streptococcus pyogenes, four Staphylococcus aureus, one Escherichia coli, and four polymicrobial infection. In-hospital mortality rate was 22.73%. Conclusions: We examined the correlation between our results, amputation rates and mortality with LRINEC score and time to surgery. However, we found no significant relationship unlike some other studies. Nevertheless, a multidisciplinary approach with radical debridement and antibiotic therapy remains the treatment cornerstone. Our hospital stays, outcomes and mortality rates align with our literature review, confirming high morbimortality despite early and appropriate intervention. Resumen: Introducción: Las infecciones necrotizantes de partes blandas (NSTI), suponen un riesgo significativo de morbimortalidad. Debido a sus síntomas inespecíficos, es crucial mantener un alto índice de sospecha. El tratamiento implica un enfoque multidisciplinar con antibióticos de amplio espectro, desbridamiento quirúrgico precoz y radical y soporte vital. En este estudio, analizamos las características clínicas y demográficas, complicaciones y el tratamiento de las NSTI en un hospital de Madrid, España. Material y métodos: Se realizó un estudio observacional retrospectivo incluyendo a todos los pacientes con NSTI intervenidos en nuestro centro desde enero de 2016 hasta diciembre de 2022, donde se analizaron los datos epidemiológicos y clínicos. La escala Laboratory risk indicator for Necrotizing fasciitis (LRINEC) se calculó de manera prospectiva para todos los pacientes. Resultados: Se incluyeron 22 pacientes (16 hombres, seis mujeres; edad media 54,8). El tiempo medio desde el inicio de los síntomas hasta la consulta en urgencias fue de 3,5 días. Todos los pacientes presentaban dolor resistente al tratamiento y 16 presentaban fiebre mayor de 37,8 °C (72,7%). Presentaban lesiones cutáneas 12 pacientes (54,5%) y 13 hipotensión y taquicardia (59,1%). El tratamiento consistió en soporte vital, antibioterapia y desbridamiento radical. El tiempo medio hasta la cirugía fue de 8,25 horas. Los cultivos intraoperatorios fueron positivos en 20 pacientes: 12 Streptococcus pyogenes, cuatro Staphylococcus aureus y uno Escherichia coli. En cuatro casos la infección fue polimicrobiana. La mortalidad intrahospitalaria fue del 22,73%. Conclusiones: El enfoque multidisciplinar, incluyendo desbridamiento radical y terapia antibioterapia, sigue siendo la piedra angular del tratamiento de las NSTI. En este estudio no encontramos correlación significativa entre nuestros resultados, tasas de amputación y mortalidad con la puntuación de la escala LRINEC ni el tiempo hasta la cirugía. Nuestros resultados, estancia hospitalaria y tasa de mortalidad coinciden con lo reportado por la literatura, confirmando la alta morbimortalidad de estas infecciones a pesar del tratamiento precoz.